HIV cure research in the time of COVID-19 - Antiretroviral therapy treatment interruption trials: A discussion paper - S. Fidler; S. Lewin; S. Deeks; O.S. Sogaard; L. Vandekerckhove; S. Collins; D. Kelly; J. Singh; M. Caskey; J. Frater (Elsevier, 2021)
This discussion paper addresses the safety of HIV cure studies, particularly those involving stopping antiretroviral therapy, known as an analytic treatment interruption (ATI) in the context of the SARS-CoV-2 pandemic. More than 30 studies listed on ClinicalTrials.gov include an ATI and many others were planned to begin over the next 12 months but most were halted due to the COVID-19 pandemic. We consider the ethics, risks and practical considerations to be taken into account before re-opening HIV cure clinical trials, noting the specific risks of ATI in the context of circulating SARS-CoV-2.